Informal Caregivers' Experiences and Needs When Caring for a Relative With Heart Failure: An Interview Study. Issue 4 (July 2016) - Gusdal, Annelie K.; Josefsson, Karin; Adolfsson, Eva Thors; Martin, Lene
Abstract : Background: Informal caregivers play an important role for persons with heart failure in strengthening medication adherence, encouraging self-care, and identifying deterioration in health status. Caring for a relative with heart failure can affect informal caregivers' well-being and cause caregiver burden. Objective: The objective of this study was to explore informal caregivers' experiences and needs when caring for a relative with heart failure living in their own home. Methods: The study has a qualitative design with an inductive approach. Interviews were conducted with 14 informal caregivers. Data were analyzed using qualitative content analysis. Results: Two themes emerged: "living in a changed existence" and "struggling and sharing with healthcare." The first theme describes informal caregivers' experiences, needs, and ways of moving forward when living in a changed existence with their relative. Informal caregivers were responsible for the functioning of everyday life, which challenged earlier established roles and lifestyle. They experienced an ever-present uncertainty related to the relative's impending sudden deterioration and to lack of knowledge about the condition. Incongruence was expressed between their own and their relative's understanding and acceptance of the heart failure condition. They also expressed being at peace with their relative and managed to restore new strength and motivation to care. The second theme describes informal caregivers' experiences, needs, and ways in which they handled the healthcare. They felt counted upon but not accounted for, as their care was taken for granted while their need to be seen and acknowledged by healthcare professionals was not met. Informal caregivers experienced an ever-present uncertainty regarding their lack of involvement with healthcare. The lack of involvement with healthcare had a negative impact on the relationship between informal caregivers and their relative due to the mutual loss of important information about changes in medication regimens and the relative's symptoms and well-being. Another cause of negative impact was the lack of opportunity to talk with healthcare professionals about the emotional and relational consequences of heart failure. Healthcare professionals had provided them neither with knowledge on heart failure nor with information on support groups in the municipality. Informal caregivers captured their own mandate through acting as deputies for their relative and claiming their rights of involvement in their relative's healthcare. They also felt confident despite difficult circumstances. The direct access to the medical clinic was a source of relief and they appreciated the contacts with the registered nurses specialized in heart failure. Informal caregivers' own initiatives to participate in meetings were positively received by healthcare professionals. Conclusions: Informal caregivers' daily life involves decisive changes that are experienced as burdensome. They handled their new situations using different strategies to preserve a sense of "self" and of "us." Informal caregivers express a need for more involvement with healthcare professionals, which may facilitate informal caregivers' situation and improve the dyadic congruence in the relation with their relative.